The Book of PF : a No-Nonsense Guide to the OpenBSD Firewall - Hansteen, Peter N. M. (No Starch Press, 2015)
With more and more services placing high demands on bandwidth and an increasingly hostile Internet environment, no sysadmin can afford to be without PF expertise. This 3rd edition covers the most up-to-date developments in PF, including new content on IPv6, dual stack configurations, the "queues and priorities" traffic-shaping system, NAT and redirection, wireless networking, spam fighting, failover provision ing, logging, and more. You'll learn how to: create rule sets for all kinds of network traffic; set up wireless networks with access points, and lock them down using authpf and special access restrictions; maximize flexibility and service availability via CARP, relayd, and redirection; build adaptive firewalls; harness OpenBSD's latest traffic-shaping system to keep your network responsive, and convert your existing ALTQ configurations to the new system; and stay in control of your traffic with monitoring and visualization tools (including NetFlow). --